Potential Challenges in Anti-angiogenic Nanotherapies and Conclusion - Mukherjee S.; Madamsetty V.S. (My University, 2025)
Since last few decades, several nanoparticles-based medicines were tested and clinically used for various biomedical applications including cancer (Mukherjee et al. in Theranostics 9:7730–7748, 2019, [1]; Mukherjee et al. Adv Funct Mater 30(35) 2003054, 2019, [2]). Unfortunately, many nanoparticles-based materials demonstrate short-term or long-term toxicity in human or environmental species. © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.